(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: The rate of heart failure in Hadhramout is steadily increasing. Objective: To determine the clinical characteristic and the predictors of in –hospital mortality of heart failure patients. Method: The first 100 consecutive patients with heart failure admitted to Ibn Seena central hospital in Mukalla for whom clinical history, physical examination and the basic investigations( including hemogram, blood sugar, chest X-Ray. Renal function test, serum cholesterol, electrocardiogram and echocardiogram) were performed during the period from October 2007 to June 2008. Results: In this study, we found male were more affected than female (65% versus 35%). The mean age of the patients was 57 ±12.1 years for males and 59 ±12.2 years for females. The most common underlying causes in all the patients were IHD in 52% followed by AHT 25%. IHD was more in males and AHT was more in females, while valvular heart diseases was the cause of HF in only 7%. The most common associated co-morbidities were renal dysfunction, anemia, dyslipidemia, diabetes mellitus and stroke in 43%, 41%, 35%, 25% and12% respectively. Patients of heart failure with impaired left ventricular function were 67.8%. And it was more in males than in females (52.7% &15.1%). The most common presenting symptoms was dyspnea of different classes in all of the patients and the most common sign was cardiomegaly in 89% of the patients followed by pulmonary crackles in 82%. And the most common arrhythmia were ventricular ectopic in 28% and atrial fibrillation in 21%. During the admission period 9 out of 100 patients died. The most common underlying causes were IHD, AHT and DCM and the most common co-morbidities of death were elder age of the patients, male sex, anemia, renal failure, DM, Stroke, impaired systolic ventricular function, and class IV NYHA dyspnea. Conclusion: This study revealed that HF is common in our community and it is recommended that early detection and management of the underlying etiology and associated co-morbidities could reduce the morbidity and mortality of HF Key words: Heart failure, clinical presentation, predictors, outcome. Mukalla, Yemen